On multiple soliton solutions of the extended (3+1)-dimensional Jimbo–Miwa equations - Mukam, Serge Paulin T.; Abbagari, Souleymanou; Houwe, Alphonse; Kuetche, Victor K.; Doka, Serge Y.; Bouetou, Thomas B.; İnç, Mustafa (Shanghai Jiaotong University, 2022)
In this paper, we deal with a set of equations, namely the extended (3 + 1)-dimensional Jimbo–Miwa (JM) equations. We focus on the calculations of soliton solutions to the aforementioned equations using the multiple exponential function method (MEF). As a result, we derive up the one to three-wave soliton solution to the both equations, while presenting the profiles obtained through the constant values related to those solutions. It is noteworthily to point out that, all the calculations in this paper are made with software package Maple. Also, the profiles of the waves depend on the arbitrary values of autocephalous parameters. © 2022
Keywords: Extended (3 + 1)-dimensional Jimbo–Miwa equation; Multiple exponential function method; Soliton solutions